Study of Factors Affecting Wireless Power Transmission Using a Double-Transmitter-Coil - ชัยดี เอกชัย; โวหาร ภาณุพงศ์; แก้วถึง วัตมล (RMUTL Engineering Journal, 2017)
To increase the power output of multiple wireless power transmission and thus investigate factors affecting the wireless power transmission. The objective of this study was to study and analyze factors affecting wireless power transmission using a double-transmitter-coil. Analyzing an equivalent circuit showed that the affecting parameters are input voltage, load resistance, mutual inductance and resonance frequency. A wireless power transmission circuit driven by a full bride inverter was designed. The designed experiment was focused on mutual inductance and resonance frequency which were more potentially changeable than other parameters. The results from this study showed that 1) The number of transmitter- coils, the directions of electric current and a proper position of transmitter-coil affected mutual inductance 2) A double-transmitter-coil at an optimal distance position increased the power output and the efficiency of wireless power transmission 3) Adjusting of frequency resonance following the change of distance, position of transmitters increased the power output and the efficiency of wireless power transmission. The findings of this study could be utilized as a guideline for further study and development relating to wireless power transmission